(Non-)Paranoid Reading of Sigmund Freud and the Fear of Being Photographed: Corpus-Based Approach - Illia Ilin (Eidos. A Journal for Philosophy of Culture)
The article delves into the question of Freud’s concept of reading, and the fear of being photographed based on an analysis of the article “A Case of Paranoia Running Counter to the Psychoanalytic Theory of That Disease” (1915). Freud explicitly guides readers on how to read and not read this text. In alignment with contemporary concepts of paranoid and non-paranoid reading in philosophy, the former encourages suspicion, undermining the integrity of the text, while seeking hidden meanings. In contrast, the latter places trust in the text and its author, focusing on the empirically observable surface of the text. This study poses a key question: how does one non-paranoically read a text that describes suspicion (Freud’s in this case) regarding his patient, a woman supposedly experiencing the fear of being photographed? To address this question, corpus linguistics, science of terminology, and distant reading are employed. Corpus linguistics and terminology help construct the concept of paranoid reading from the body of Freud’s work published before the specified article. Distant reading enables a non-paranoid reading of Freud’s text, situating it within the context of other texts from late nineteenth to early twentieth-century Austria that discuss the fear of being photographed.